Design and Implementation of a Digital Police Assistance Application for Enhancing Public Services - Rio Martin Rio; Nia Oktaviani; Evi Yulianingsih (Journal of Information System and Artificial Intelligence, 2026)
Public service delivery in law enforcement is often hindered by limited accessibility, manual procedures, and lack of transparency in complaint handling. This study proposes the Digital Police Assistance Application, a mobile platform designed to integrate incident reporting, real-time tracking, information dissemination, and an administrative dashboard for police officers. The system was developed using the Waterfall model with Flutter for cross-platform mobile development, Node.js with Express for backend services, and MySQL for data storage. Functional validation through Black Box testing confirmed that all modules operated as intended. Usability evaluation involving 30 participants (15 citizens and 15 police officers) employed the System Usability Scale (SUS). The application achieved an average SUS score of 82.5, categorized as “Excellent,” with citizens scoring slightly higher (84.2) than police officers (80.7). Citizens appreciated the simplicity and transparency of complaint tracking, while police officers highlighted dashboard efficiency and suggested integration with internal databases. These results demonstrate that the application is both functional and user-friendly, with strong potential to enhance transparency, efficiency, and trust in police services. Future work will address system interoperability, security improvements, and pilot testing across multiple jurisdictions